Market versus formula-derived prices for segregated early-weaned pigs - Dhuyvetter, Kevin C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A formula for deriving the price of segregated early-weaned (SEW) pigs using prices of grain, soybean meal, and market hog was estimated based on return on investment being equal for all three phases of production—farrowing, nursery, and finishing. The USDA- reported SEW pig prices were compared with formula-derived prices. The level of correlation between these two series was sensitive to how prices of grain, soybean meal, and market hog were chosen. Using expected prices in the formula resulted in SEW prices that were correlated strongly with reported market prices. Using hindsight cash prices in the formula resulted in SEW formula prices that were correlated weakly with reported prices. This approach may be appropriate with contractual relationships where the goal is to share profits and losses proportionately. Thus, the manner in which the formula is used (i.e., method of choosing prices) will depend on the risk attitudes of the buyer and seller, as well as the nature of their business relationship.
Keywords: Swine; SEW prices; Formula prices; Marketing